PELATIHAN PENGGUNAAN LAPTOP DAN ATAU HP YANG EFEKTIF UNTUK ORANG TUA PENDAMPING SISWA - Wahjudi, Rudy Setya; Sulaiman, Susan (Jurnal Serina Abdimas, 2024)
Various educational techniques and continuous practices are indispensable for success in education, since the quality of education serves to build the character of the student to become a moral and virtuous human being based on faith in a good personality. In today's learning, the use of existing technologies requires creativity and sufficient ability whereas in reality the use of existing media or technology cannot be maximized by some educators, as a result of which the use of such media or technology in learning has not been obtained to the maximum. Computers as a technology and interactive learning medium of teachers with students, are able to make students more active, creative, learning to be fun, not boring, and increase students' interest in learning, so its existence is needed to better support the formation of active, insightful and up-to-date individuals. Parents who accompanying students in the process of studying at home are also obliged to understand and follow the development of information technology. As a solution to the problem, a Training on the Use of a Laptop or HP was conducted for the student’s accompanying parents, which includes how to operate a laptop or HP, how to access the Internet and use application programs. Implementation is carried out online using teamlink. The evaluation was conducted through the Satisfaction Questionnaire in which 92.5% of the participants were satisfied and rated the satisfaction scale  ≥4 from a scale of 1 to 5 while 92.5% of participants were satisfied by rating a satisfaction scale of ≥4 on the performance of the instructor and as many as 90% of the participants on the performance of the assistant. The before and after training tests gave results that the skill in using laptops and mobile phones of the participants increase by an average of 80%. ABSTRAK Berbagai teknik mendidik maupun praktek yang berlangsung terus menerus sangat diperlukan untuk keberhasilan dalam pendidikan, karena mutu pendidikan berfungsi untuk membentuk watak anak didik agar menjadi manusia berakhlak dan berbudi luhur yang didasarkan pada iman dalam kepribadian yang baik.. Dalam pembelajaran dewasa ini, pemanfaatan teknologi yang ada memerlukan  kreativitas dan kemampuan yang memadai sedangkan  pada kenyataanya penggunaan media ataupun teknologi yang ada belum dapat dimanfaatkan secara maksimal oleh sebagian pendidik,, akibatnya penggunaan dari media atau teknologi tersebut dalam pembelajaran belum dapat diperoleh secara maksimal. Komputer sebagai teknologi dan media pembelajaran interaktif guru dengan siswa, mampu menjadikan siswa lebih aktif, kreatif, belajar menjadi menyenangkan, tidak membosankan, dan meningkatkan minat belajar siswa, sehingga diperlukan keberadaanya untuk lebih menunjang dalam pembentukan individu yang aktif, berwawasan dan mengikuti perkembangan jaman. Orang tua murid sebagai pendamping siswa dalam proses belajar di rumah juga wajib memahami dan mengikuti perkembangan teknologi informasi. Sebagai solusi dari permasalahan yang dihadapi, dilakukan  Pelatihan Penggunaan Laptop atau HP untuk orang tua pendamping siswa yang memuat cara mengoperasionalkan laptop atau HP, cara akses internet dan menggunakan program aplikasi. Pelaksanaan dilakukan secara daring menggunakan teamlink. Evaluasi dilakukan melalui Kuesioner Kepuasan di mana 92,5% peserta merasa puas dan memberi nilai skala kepuasan  dari skala satu hingga 5.  Penilaian skala kepuasan   diberikan oleh  92,5%  peserta terhadap kinerja instruktur  dan 90% peserta terhadap kinerja asisten. Tes sebelum dan sesudah pelatihan memberikan hasil para peserta mendapatkan peningkatan ketrampilan dalam penggunaan laptop dan HP rata-rata 80%.